Sphingosine 1‐phosphate is a ligand for peroxisome proliferator‐activated receptor‐γ that regulates neoangiogenesis. Issue 9 (18th May 2015) - Parham, Kate A.; Zebol, Julia R.; Tooley, Katie L.; Sun, Wai Y.; Moldenhauer, Lachlan M.; Cockshell, Michaelia P.; Gliddon, Briony L.; Moretti, Paul A.; Tigyi, Gabor; Pitson, Stuart M.; Bonder, Claudine S.
ABSTRACT: Sphingosine 1‐phosphate (S1P) is a bio‐active lipid that can function both extracellularly and intracellularly to mediate a variety of cellular processes. Using lipid affinity matrices and a radiolabeled lipid binding assay, we reveal that S1P directly interacts with the transcription factor peroxisome proliferator‐activated receptor (PPAR) γ. Herein, we show that S1P treatment of human endothelial cells (ECs) activated a luciferase‐tagged PPAR‐γ‐specific gene reporter by ~12‐fold, independent of the S1P receptors. More specifically, in silico docking, gene reporter, and binding assays revealed that His323 of the PPAR‐γ ligand binding domain is important for binding to S1P. PPAR‐γ functions when associated with coregulatory proteins, and herein we identify that peroxisome proliferator‐activated receptor‐γ coactivator 1 (PGC1)β binds to PPAR‐γ in ECs and their progenitors (nonadherent endothelial forming cells) and that the formation of this PPAR‐γ:PGC1β complex is increased in response to S1P. ECs treated with S1P selectively regulated known PPAR‐γ target genes with PGC1β and plasminogen‐activated inhibitor‐1 being increased, no change to adipocyte fatty acid binding protein 2 and suppression of CD36. S1P‐induced in vitro tube formation was significantly attenuated in the presence of the PPAR‐γ antagonist GW9662, and in vivo application of GW9662 also reduced vascular development in Matrigel plugs. Interestingly, activation of PPAR‐γ by the synthetic ligand troglitazone also reduced tube formation in vitro and in vivo. To support this, Sphk1 ‐/‐ Sphk2 +/‐ mice, with low circulating S1P levels, demonstrated a similar reduction in vascular development. Taken together, our data reveal that the transcription factor, PPAR‐γ, is a bona fide intracellular target for S1P and thus suggest that the SlP:PPAR‐γ:PGC1β complex may be a useful target to manipulate neovascularization.—Parham, K. A., Zebol, J. R., Tooley, K. L., Sun, W. Y., Moldenhauer, L. M., Cockshell, M. P., Gliddon, B. L., Moretti, P. A., Tigyi, G., Pitson, S. M., Bonder, C. S. Sphingosine 1‐phosphate is a ligand for peroxisome proliferator‐activated receptor‐γ that regulates neoangiogenesis. FASEB J. 29, 3638‐3653 (2015). www.fasebj.org